A new companion to Chaucer - Brown, Peter, 1948- (Blackwell companions to literature and culture, 2019)
The extensively revised and expanded version of the acclaimed Companion to Chaucer An essential text for both established scholars and those seeking to expand their knowledge of Chaucer studies, A New Companion to Chaucer is an authoritative and up-to-date survey of Chaucer scholarship. Rigorous yet accessible, this book helps readers to identify current debates, recognize historical and literary context, and to understand how particular concepts and theories affect the interpretation of Chaucer's texts. Chaucer specialists from around the globe offer contributions that range from updates of long-standing scholarship on biography, language, women, and social structures, to original research in new areas such as ideology, the afterlife, patronage, and sexuality. In presenting conflicting perspectives and ideological differences, this stimulating volume encourages readers to explore additional paths of inquiry and engage in lively and informed debate. Each chapter of the Companion, organized by issues and themes, balances textual analysis and cultural context by grounding the reader in existing scholarship. Key issues from specific passages are discussed with an annotated bibliography provided for reference and further reading. Compiled with all students of Chaucer in mind, this important volume: Presents contributions from both established and emerging specialists Explores the circumstances in which Chaucer wrote, such as the political and religious issues of his time Includes numerous close readings of selected poems Provides points of entry to a wide range of approaches to Chaucer's works Incorporates original research, fresh perspectives, and updated additions to Chaucer scholarship A New Companion to Chaucer is a valuable and enduring resource for scholars, teachers, and students of medieval literature and medieval studies, as well as the general reader interested in interpretations and historical contexts of Chaucer's writings.